Accelerated reactive dissolution model of drug release from long-acting injectable formulations - Sonntag, Erik; Kolář, Jiří; Djukaj, Suada; Lehocký, Róbert; Štěpánek, František (European journal of pharmaceutics and biopharmaceutics, 2023)
Long-acting injectable formulations represent a rapidly emerging category of drug delivery systems that offer several advantages compared to orally administered medicines. Rather than having to frequently swallow tablets, the medication is administered to the patient by intramuscular or subcutaneous injection of a nanoparticle suspension that forms a local depot from which the drug is steadily released over a period of several weeks or months. The benefits of this approach include improved medication compliance, reduced fluctuations of drug plasma level, or the suppression of gastrointestinal tract irritation. The mechanism of drug release from injectable depot systems is complex, and there is a lack of models that would enable quantitative parametrisation of the process. In this work, an experimental and computational study of drug release from a long-acting injectable depot system is reported. A population balance model of prodrug dissolution from asuspension with specific particle size distribution has been coupled with the kinetics of prodrug hydrolysis to its parent drug and validated using in vitro experimental data obtained from an accelerated reactive dissolution test. Using the developed model, it is possible to predict the sensitivity of drug release profiles to the initial concentration and particle size distribution of the prodrug suspension, and subsequently simulate various drug dosing scenarios. Parametric analysis of the system has identified the boundaries of reaction- and dissolution-limited drug release regimes, and the conditions for the existence of a quasi-steady state. This knowledge is crucial for the rational design of drug formulations in terms of particle size distribution, concentration and intended duration of drug release.
Keywords: Nanosuspension; Particle size distribution; injekce intramuskulární; Reactive dissolution; Prodrugs; Suspensions; Hydrolysis; rozpustnost; Paliperidone palmitate; suspenze; lidé; Delayed-Action Preparations; prekurzory léčiv; Humans; léky s prodlouženým účinkem; Drug Liberation; Antipsychotic Agents; uvolňování léčiv; Injections, Intramuscular; Injectable depot systems; Solubility; antipsychotika